The effect of ursolic acid on leishmania (Leishmania) amazonensis is related to programed cell death and presents therapeutic potential in experimental cutaneous leishmaniasis - Yamamoto, Eduardo S. (2018)
PMID: 26674781 WOS:000366722700076